E. Aubert de la Rue, Brésil aride (La vie dans la caatinga), 6º édition, Paris, Gallimard (Col. Deffontaines), 1957, 244 p. - M. Z. (1958)
Fil: M. Z.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras